The Influence of Information Services Using Animated Media on Anti-Bullying Attitudes in Class VIII Students of SMP N 1 Sedayu Academic Year 2023/2024 - Lilief Ainur Nastaiin; Enik Nurkholidah; Arum Setiowati (Universitas Negeri Semarang, 2024)
This research is motivated by the many bullying tragedies that occur at school by peers which cause deep trauma for victims of bullying. The aim of this research is to increase anti-bullying awareness among students and the influence of animated media information services on anti-bullying attitudes. This research uses a quantitative approach with correlational methods. The population of this study is grade VIII students of SMP N 1 Sedayu for the 2023/2024 Academic Year which amounts to 126 students. The sample in this study took 63 students using probability sampling techniques with the type of sampling or random or random sampling. The data collection method in this study used questionnaires. Data analysis techniques using simple regression tests. The results showed that the accepted hypothesis and information services using animation media had a positive and significant effect on anti-bullying attitudes in grade VIII students of SMP N 1 Sedayu for the 2023/2024 academic year. From the results of a simple regression test, it is known that the R Square value of 0.221 means that information services using animation media have an effect on anti-bullying attitudes. It is expected that guidance and counseling teachers will provide information services with a variety of interesting media so that students can more easily understand and remember. Penelitian ini dilatarbelakangi oleh banyaknya tragedi bullying yang terjadi di sekolah oleh teman sebaya yang menyebabkan trauma mendalam bagi korban bullying. Tujuan dari penelitian ini adalah meningkatkan kesadaran anti bullying pada siswa serta pengaruh layanan informasi media animasi terhadap sikap anti bullying. Penelitian ini menggunakan pendekatan kuantitatif dengan metode korelasional. Populasi penelitian ini adalah siswa kelas VIII SMP N 1 Sedayu Tahun Ajaran 2023/2024 yang berjumlah 126 siswa. Sampel dalam penelitian ini mengambil 63 siswa dengan menggunakan teknik probability sampling dengan jenis pengambilan sampel atau acak atau random sampling. Metode pengumpulan data dalam penelitian ini menggunakan angket. Teknik analisis data dengan menggunakan uji regresi sederhana. Hasil penelitian menunjukkan bahwa hipotesis diterima dan layanan informasi dengan menggunakan media animasi berpengaruh positif dan signifikan terhadap sikap anti bullying pada siswa kelas VIII SMP N 1 Sedayu tahun pelajaran 2023/2024. Dari hasil uji regresi sederhana diketahui nilai R Square sebesar 0,221 berarti layanan informasi dengan menggunakan media animasi berpengaruh terhadap sikap anti bullying. Diharapkan guru bimbingan dan konseling untuk memberikan layanan informasi dengan berbagai media yang menarik agar siswa lebih mudah memahami dan mengingat.